Corticosterone, inflammation, immune status and telomere length in frigatebird nestlings facing a severe herpesvirus infection - Sebastiano, Manrico (Conserv Physiol, 2017)
Herpesvirus outbreaks are common in natural animal populations, but little is known about factors that favour the infection and its consequences for the organism. In this study, we examined the pathophysiological consequences of a disease probably attributable to herpesvirus infection for several markers of immune function, corticosterone, telomere length and inflammation. In addition, we assessed whether any markers used in this study might be associated with the occurrence of visible clinical signs of the disease and its impact on short-term survival perspectives. To address our questions, in spring 2015, we collected blood samples from nestlings of the magnificent frigatebird (Fregata magnificens) that were free of any clinical signs or showed visible signs of the disease. We found that the plasma concentration of haptoglobin was strongly associated with the infection status and could predict probabilities of survival. We also found that nestlings with clinical signs had lower baseline corticosterone concentrations and similar telomere length compared with healthy nestlings, whereas we did not find any association of the infection status with innate immune defenses or with nitric oxide concentration. Overall, our results suggest that the plasma concentration of haptoglobin might be a valuable tool to assess survival probabilities of frigatebird nestlings facing a herpesvirus outbreak.